Humanitarian Crises and the Management of the Internally Displaced Persons’ (IDPs) Camps in Nigeria - Oladeji, Abubakar (African Journal of Stability and Development (AJSD), 2018)
Given the high level of humanitarian crises in Nigeria, African’s largest and most populous country, particularly over the past ten years, the concept of Internally Displaced Persons (IDPs) Camps has gained some currency in several parts of the country. In the main, IDPs Camps, which have become a necessity in Nigeria, are characterised by increasing social injustices like rape, diversion of food items and other corruption-related cases which are deemed as inexcusable. As a consequence, IDPs in Nigeria suffer disproportionately from different problems such as malnutrition, sickness, insecurity in the camps, lack of access to education and healthcare, among others. Many have suffered severe mental distress caused by traumatic experiences of having witnessed or been subjected to gross violations of human rights such as killings, torture, sexual violence, family separation and displacement from home. For all these categories of victims, the idea of seeking refuge, protection and succour in IDPs Camps may not be a bad one. However, the management of these camps in Nigeria has become a source of great concern due to heart-rending stories of sorrow and shame in Nigeria’s IDPs Camps. This paper examines some dark spots in the management of IDPs Camps in Nigeria and concludes that the vulnerability of displaced persons is a major reason why sustainable strategies for rehabilitation must be considered and implemented at the shortest possible time. Key words: Humanitarian Crisis, Internally Displaced Persons (IDPs) Camps, Vulnerability, Insecurity and Corruption.